Islamic Philosophy in Contemporary Iran - Muhammad Fanaie Ishkawari (حکمت اسرا)
History bears witness to the fact that Islamic Iran was always a cradle for wisdom and philosophical thought. The great sages and mystics of this land—from FÁrÁbÐ to Ibn SÐnÁ, MawlÁnÁ RÙmÐ to SuhrawardÐ, and Sayyid Íaydar ÀmulÐ to MullÁ ÑadrÁ—are known the world over as the torchbearers of knowledge and spirituality. It is no accident that traditionally the seekers of knowledge in all corners of the world would look to the prodigies of Iran for such wisdom; hence traces of the works of these Islamic-Iranian authors can be found in the East and the West. But is this honour a historical phenomena and a thing of the past? Or is this lamp still lit? In response it can be said that while the flame has flickered and has given off light of different intensities, it has never been extinguished and continues to give light even today. An overall awareness of the philosophical life of contemporary Iran—by introducing the leaders of this movement to all seekers of knowledge in and outside of Iran—is beneficial and can only but help in the continuation of this rich tradition. Moreover, it is a necessary step insofar as it provides posterity with access to a most valued heritage. The present study is an overview of the intellectual life of some of the leading figures of Islamic philosophy in contemporary Iran.